Interhospital variability in Out-of-Hospital cardiac arrest survival in a large metropolitan area - Pavitra Kotini-Shah; Nicole Blum; Shaveta Khosla; Joseph Weber; Eddie Markul; Katie Tataris; Teri Campbell; Terry Vanden Hoek; Marina Del Rios (Resuscitation Plus, 2023)
Background: Out-of-hospital cardiac arrest (OHCA) survival varies widely across the United States. The impact of hospital OHCA volume and ST-elevation myocardial infarction (STEMI) Receiving Center (SRC) designation on survival is not fully understood. Methods: This was a retrospective analysis of adult OHCA who survived to hospital admission reported to the Chicago Cardiac Arrest Registry to Enhance Survival (CARES) database from May 1, 2013 to December 31, 2019. Hierarchical logistic regression models were generated and adjusted by hospital characteristics. Survival to hospital discharge (SHD) and cerebral performance category (CPC) 1–2 at each hospital were calculated after adjusting for arrest characteristics. Hospitals were assigned quartiles (Q1-Q4) based on total arrest volume to allow for comparison of SHD and CPC 1–2 between quartiles. Results: 4,020 patients met inclusion criteria. 21 of the 33 Chicago hospitals included in this study were designated SRCs. Adjusted SHD and CPC 1–2 rates ranged from 27.3% to 37.0% and from 8.9% to 25.1%, respectively, by hospital. SRC designation did not significantly affect SHD (OR 0.96; 95% CI, 0.71–1.30) nor CPC 1–2 (OR 1.17; 95% CI, 0.74–1.84). OHCA volume quartiles did not significantly affect SHD (Q2: OR 0.94; 95% CI, 0.54–1.60; Q3: OR 1.30; 95% CI, 0.78–2.16; Q4: OR 1.25; 95% CI, 0.74–2.10) nor CPC 1–2 (Q2: OR 0.75; 95% CI, 0.36–1.54; Q3: OR 0.94; 95% CI, 0.48–1.87; Q4: OR 0.97; 95% CI, 0.48–1.97). Conclusion: Interhospital variability in both SHD and CPC 1–2 cannot be explained by hospital arrest volume nor SRC status. Further research is warranted to explore reasons for interhospital variability.